HUBUNGAN TINGKAT PENGETAHUAN DENGAN PARTISIPASI PADA PEMERIKSAAN PAP SMEAR PADA WANITA PEKERJA SEKS KOMERSIAL - Kurniawan, Bayu; Asmika, Asmika; Sarwono, Imam (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT Carcinoma cervix is the most frequent malignancy and the highest cancer mortality rate in women worldwideas well as in Indonesian. From 4.290 of cervical carciona in Indonesia , 1.326 cases were found in SurabayaOver 70% patients were in the advanced stadium. Pap Smear as a screening test is a prevention strategy focarcinoma cervix. Sex worker has a high risk for carcinoma cervix. This research was carried out in GangDolly Prostitution Area Surabaya aimed to describe the characteristics of sex worker and the correlationbetween knowledge level and participation in Pap Smear examination . A cross sectional approach wasconducted with 67 respondents. The variables: characteristics, knowledge level and pap-smear participationwas measured by open and close-ended questionnaire guided by the researcher. The data were presentedas cross tabulation and further testing the correlation based on Lambda Correlation test (α = 0,05). Theresults showed an equal proportion of good and sufficient knowledge and only limited respondent (2,99%who have very poor knowledge. 89,55% respondents have had done their Pap Smear examination, fromthose mostly were respondents with sufficient knowledge (41,79%). There was a weak and not significancorrelation between respondent’s knowledge level about carcinoma cervix and their participation in PapSmear examination (Lambda Correlation test, Lb = 0,286, approx. sig. = 0,151). Keywords : Knowledge , Carcinoma Cervix, Pap Smear, Participation